USING INSTAGRAM AS SOCIAL MEDIA MARKETING FOR CAFE RED COFFEE AND PLANTS - Moch Rizky Adi Nugroho; Nur Maghfirah Aesthetika (International Journal of Economic Integration and Regional Competitiveness, 2024)
General Background: In the competitive landscape of the café industry, social media, particularly Instagram, has emerged as a pivotal tool for business development and consumer engagement. Specific Background: This study focuses on Red Coffee and Plants, which leverages Instagram to disseminate information and attract consumers, highlighting the platform's effectiveness in marketing strategies. Knowledge Gap: Despite the growing recognition of social media marketing, there is a lack of comprehensive analysis regarding the specific dimensions of social media marketing utilized by local cafes on platforms like Instagram. Aims: The primary aim of this research is to explore and identify the dimensions of social media marketing present in the Instagram account @redcoffee.id. Results: Utilizing qualitative methods, including purposive sampling and observations of the Instagram account, data was analyzed through the techniques outlined by Miles & Huberman—encompassing data reduction, presentation, and conclusion drawing. The findings reveal four key dimensions of social media marketing: interaction, share of content, accessibility, and credibility. Novelty: This study contributes to the understanding of how local cafés can effectively use social media marketing dimensions to enhance consumer engagement and brand loyalty. Implications: The results underscore the importance of these marketing dimensions for café owners seeking to optimize their Instagram presence, suggesting that a strategic approach to social media can significantly enhance brand visibility and consumer relationships. This research provides valuable insights for practitioners aiming to develop effective social media marketing strategies in the café sector.